Eyes, Soul, Heart and Other Containers - Būdvytytė, Aina; Toleikienė, Reda (Respectus Philologicus, 2003)
The idea of the article is based on the assumption that the analysis of certain language items representing the concepts of SOUL and BODY in Lithuanian and German can reveal the fixed images and associations relating to body parts and inner psychical states and processes. CONTAINER imagery schema conceptual metaphor is discussed. The concept of CONTAINER gives for conceptualization of abstract entities because it has a simple structure showing the entity inside a container. Container experience is one of the earliest human experiences. Abstract phenomena that cannot be experienced sensorily are understood and verbalized according to the features: relation to/out of, inside/outside, the content of a container, closed/open, that are realized in the languages under investigation differently. Secrecy, seclusion, hard getting inside are characteristic of SOUL and HEART images.